Should all athletes use the same twisting strategy? The role of anthropometry in the personalisation of optimal acrobatic techniques - Charbonneau, E.; Sechoir, L.; Pascoa, F.; Begon, M. (Sports Biomechanics, 2025)
Choosing the best acrobatic technique for each athlete remains a challenge for coaches. Predictive simulations may support coaches, but only a few athlete morphologies have been simulated yet. It is assumed that the optimal acrobatic techniques are somehow generalisable across athletes. However, anthropometry characteristics can influence the twist rotation outcome of an acrobatic technique. Our objective was to assess the differences in optimal techniques caused by the anthropometric differences between athletes. Anthropometry-specific techniques of double pike forward somersaults ending with 1 1/2 or 2 1/2 twists were generated using predictive simulations and the measurements of 18 acrobatic athletes presenting a wide range of anthropometry. We found that anthropometry had an impact on the optimal acrobatic techniques by modifying the amplitude of the strategies used or, more drastically, by modifying the strategies used. Some athletes had a morphological advantage for twist creation, which was measured using the combined twist potential, a metric introduced in the current study. This metric was very strongly correlated with the complexity of the techniques; models with an advantage for twist creation needed fewer/shorter limb movements to generate twists. This research shows that coaches should consider their athletes` anthropometry to offer them better guidance.